Nurses’ motivation, knowledge and perception on compliance with standard precautions - Maria Ulfa; Mateus Sakundarno Adi; Antono Suryoputro (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Standard precautions practice is the main action in preventing and controlling infections in hospitals. Nurse compliance with standard precautions is influenced by various factors, including knowledge, perception, and motivation. Purpose: To analyze the relationship between the level of knowledge, perception, and motivation of nurses with the practice of standard precautions. Method: A quantitative approach, specially focusing on analytical survey and cross-sectional method. The study took place from December 2024-Febuary 2025 in Islamic Hospital of Muhammadiyah Medical Care Center, Pekajangan. The independent variable was knowledge, risk perception, and motivation of nurses, dependent variable is standard precautionary practices in hospitals. Using systematic random sampling and slovin formula, 173 respondents were selected, who met specific inclusion and exclusion criteria. The analysis proceeded with a univariate test to determine the frequency distribution of respondent’s characteristics, followed by bivariate analysis using spearman rank test Results: The study revealed significant factors influencing the practice of standard precautions. It showed a gender-based difference in adherence (p = 0.008), a positive relationship between the level of perception and practice (p = 0.033), and a significant association with motivation level (p = 0.01). Conclusion: Nurses generally had good to fair levels of knowledge, perception and motivation regarding standard precautions, indicating effective implementation of patient safety. Perception and motivation significantly influenced compliance, while knowledge without significant influence.